2016
DOI: 10.1364/oe.24.019949
|View full text |Cite
|
Sign up to set email alerts
|

Four-plate piezoelectric actuator driving a large-diameter special optical fiber for nonlinear optical microendoscopy

Abstract: In nonlinear optical microendoscope (NOME), a fiber with excellent optical characteristics and a miniature scanning mechanism at the distal end are two key components. Double-clad fibers (DCFs) and double-clad photonic crystal fibers (DCPCFs) have shown great optical characteristics but limited vibration amplitude due to large diameter. Besides reducing the damping of fiber cantilever, optimizing the structural of the actuator for lower energy dissipation also contributes to better driving capability. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Besides standard endoscopic optical imaging, the research team successfully demonstrated the feasibility of SFE in more complex optical imaging techniques (e.g., wide-field fluorescence, photometric stereoscopic, confocal, two-photon fluorescence and other optical imaging techniques) [ 18 , 19 ]. Wang Ying and Li Zhi replaced the circular piezo tube by combining four piezoelectric ceramic pieces into a square piezo tube to drive the cantilever fiber optic to achieve optical imaging of the sample [ 20 ]. Compared with the circular piezo tube, the square piezo tube is less costly and easier to process, but it also has the problem of insufficient driving force.…”
Section: Introductionmentioning
confidence: 99%
“…Besides standard endoscopic optical imaging, the research team successfully demonstrated the feasibility of SFE in more complex optical imaging techniques (e.g., wide-field fluorescence, photometric stereoscopic, confocal, two-photon fluorescence and other optical imaging techniques) [ 18 , 19 ]. Wang Ying and Li Zhi replaced the circular piezo tube by combining four piezoelectric ceramic pieces into a square piezo tube to drive the cantilever fiber optic to achieve optical imaging of the sample [ 20 ]. Compared with the circular piezo tube, the square piezo tube is less costly and easier to process, but it also has the problem of insufficient driving force.…”
Section: Introductionmentioning
confidence: 99%
“…Two-photon microscopy (TPM) is renowned for its remarkable capabilities in label-free, high resolution, and three-dimensional imaging [2]. The development of high-performance fiber-optic scanning nonlinear endomicroscopy has emerged as a crucial research direction in the field of miniature TPM [3][4][5][6][7]. High resolution imaging of biological tissues is imaged by detecting fluorescence signals, such as two-photon/three-photon fluorescence, second/third harmonic generation signals, and coherent anti-Stokes Raman scattering signals.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Probe-based confocal endoscopes are commonly used. They transmit laser and fluorescence images via a fiber bundle, 3 which has flexibility and accessibility for in vivo clinical imaging. The miniature objective system is the core component of confocal endoscopy for high resolution to directly visualize cells and is often assembled from multiple optical elements to correct aberrations.…”
Section: Introductionmentioning
confidence: 99%